Tracking the influence of cryogenic cooling on sensitization - Mridha, Shahjahan; Muhammed Olawale Hakeem, Amuda (s.n, 2012)
The loss of corrosion resistance in ferritic stainless steel (FSS) welds due to inter-granular precipitation of chromium carbides restricts the use of the alloy for structural application. The use of cryogenic cooling offers dual opportunities for the control of weld geometry and gain structure in FSS. This results in improved mechanical properties but the effect on carbide precipitation was not investigated.